Alexandru Sadi-Ionescu (Confluenţe Bibliologice, 2025)
In the article are presented the most important events in the life and work of Alexander Sadi-Ionescu, Romanian specialist in bibliology. His contributions in development of Romanian library science are listed: introduction of subject catalogue, publishing of bilingual Bulletin of bibliography, promoting the use of the Universal Decimal Classiﬁcation.
Keywords: Sadi-Ionescu Alexandru (1873-1926); Romanian personalities